An EWSR1-CREB3L1 Fusion Gene in Extraskeletal Undifferentiated Round Cell Sarcoma Expands the Spectrum of Genetic Landscape in the "Ewing-Like" Undifferentiated Round Cell Sarcomas. (February 2021) - Bissonnette, Caroline; Shilo, Konstantin; Liebner, David; Rogers, Alan; Pollock, Raphael E.; Iwenofu, O. Hans
The molecular findings in Ewing sarcoma have greatly expanded in recent years. Furthermore, this is particularly true for the subset termed "Ewing-like" undifferentiated round cell sarcomas in which new translocations have been reported since the fourth edition of the WHO Classification of Tumours of Soft Tissue and Bone . Amid this expanding genetic landscape, we report a case of extraskeletal undifferentiated round cell "Ewing-like" sarcoma in a 27-year-old female. The patient presented with a large lung mass accompanied on staging imaging by deposits suspicious for metastatic disease in the humerus, calvarium, and lymph nodes of the neck and chest. Biopsy of the lung mass revealed a densely packed monotonous proliferation of round, uniform neoplastic cells with scant cytoplasm. By immunohistochemistry, the tumor cells were diffusely positive for CD99, synaptophysin, TLE1, EMA, and MUC4 and negative for FLI1, PAX7, AE1/3, S100, SOX10, WT1, p63, desmin, and HMB45. Fluorescence in situ hybridization demonstrated rearrangement of the EWSR1 gene. Next-generation sequencing based assay revealed an EWSR1-CREB3L1 fusion. Taken together, the histomorphologic and molecular findings were considered consistent with an undifferentiated round cell sarcoma with an EWSR1-CREB3L1 fusion. Although described in entities such as sclerosing epithelioid fibrosarcoma, low-grade fibromyxoid sarcoma, and small cell osteosarcoma, this has not been previously described in undifferentiated round cell ("Ewing-like") sarcoma. This finding adds to the growing list of undifferentiated round cell sarcomas with Ewing-like morphologic phenotype–associated fusion genes and may contribute to further defining and characterizing the different subset of tumors in the Ewing family of tumors.